2000
DOI: 10.1037/0021-9010.85.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Employee attitude surveys: Examining the attitudes of noncompliant employees.

Abstract: Employees (N = 194) from a wide variety of organizations participated in this study aimed at describing the attitudes of individuals who refuse to respond to an employee survey request (noncompliants). Noncompliants, in comparison with those individuals who would comply with the survey request, possessed greater intentions to quit, less organizational commitment, and less satisfaction toward supervisors and their own jobs. Noncompliants also possessed more negative beliefs regarding how their organization hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
143
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(165 citation statements)
references
References 33 publications
17
143
1
1
Order By: Relevance
“…In the simulations presented in Study 2, we examine the impact of using group-retention rules when data were missing systematically. The latter approach is consistent with recent research that has suggested that nonresponse is often linearly related to the variables investigated (e.g., Rogelberg, Conway, Sederburg, Spitzmüller, Aziz, & Knight, 2003;Rogelberg, Luong, Sederburg, & Cristol, 2000).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In the simulations presented in Study 2, we examine the impact of using group-retention rules when data were missing systematically. The latter approach is consistent with recent research that has suggested that nonresponse is often linearly related to the variables investigated (e.g., Rogelberg, Conway, Sederburg, Spitzmüller, Aziz, & Knight, 2003;Rogelberg, Luong, Sederburg, & Cristol, 2000).…”
supporting
confidence: 74%
“…Moreover, our results do not address the question of which nonresponse patterns actually occur in organizational surveys. Theorizing and empirical data do suggest, however, that the nonresponse patterns that we modeled in our simulations are not unreasonable (see Allen et al, 2007a;Borg & Baumgärtner, 2008;Rogelberg et al, 2000Rogelberg et al, , 2003Williams, Allen, & Carter, 2010). Nonetheless, nonresponse can occur in countless ways, and we could not model them all.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the sample was not significantly different from employee population in terms of age, gender, organizational tenure, work status, or education, we could not estimate whether the non-response was random or not (Newman, 2009). It could be that unsatisfied employees are less willingly to cooperate with a study that has been supported by their organization (Rogelberg, Luong, Sederburg, & Cristol, 2000). However, at the same time it could be that unsatisfied employees use organizational surveys to express their opinions about the organization (Newman, 2009;Rogelberg et al, 2003).…”
mentioning
confidence: 99%
“…Those refusing explicitly to take part in organizational surveys are likely to be less committed to their organizations, less satisfied with their supervisors and more likely to quit (Rogelberg et al, 2000). Whilst the use of WBS rather than MBS may introduce response bias to questions related to technology adoption, online respondents having more developed IT skill sets (Couper, 2000), it is unclear whether differences will occur regarding other topics.…”
Section: Differences In Response Contentmentioning
confidence: 99%